The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/agronomy10010005
|View full text |Cite
|
Sign up to set email alerts
|

Response of Ancient and Modern Wheat Varieties to Biochar Application: Effect on Hormone and Gene Expression Involved in Germination and Growth

Abstract: Agriculture has changed dramatically due to mechanization, new technologies, and the increased use of chemical fertilizers. These factors maximize production and reduce food prices, but may also enhance soil degradation. Sustainable agricultural practices include altering crop varieties and the use of soil amendments to increase production, improve irrigation, and more effectively use fertilizers. Ancient and modern durum wheat varieties have been shown to be tolerant to conditions caused by climate change and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
(50 reference statements)
1
9
0
Order By: Relevance
“…The current data is in a line with Racioppi et al (2019) who evaluated the response of wheat to biochar from wood in Italy. The authors detected the impact of biochar soil amendment on gene expression using real-time polymerase chain reaction (RT-PCR).…”
Section: Cytological Studies: Mitosis Division and Aberrationssupporting
confidence: 53%
“…The current data is in a line with Racioppi et al (2019) who evaluated the response of wheat to biochar from wood in Italy. The authors detected the impact of biochar soil amendment on gene expression using real-time polymerase chain reaction (RT-PCR).…”
Section: Cytological Studies: Mitosis Division and Aberrationssupporting
confidence: 53%
“…Fahad et al and Voß et al also observed similar improvements in phytohormones in their respective studies. Application of biochar spray led to an increase in the quantities of IAA (0.94 μg/g), GA (49.1 μg/g), SA (33.2 mg/g), and ABA (30.6 mg/g) in tomato plants when applied at a dosage of 30 mg/L. , Racioppi et al observed a significant increase in the concentrations of indole-3-acetic acid (IAA) and gibberellic acid (GA) as a result of the application of biochar . The concentrations of ABA were found to be substantially lower compared to the concentrations of IAA and GA.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic responses of cultured organs are modified by enhanced adsorption of toxic metabolites and gradual release of growth-promoting compounds (Thomas 2008). Changes in transcription of development-related genes (Racioppi et al 2019) and rearrangements of endogenous phytohormone profile (von Aderkas 2002; Farhangi-Abriz and Torabian 2018) affect organogenic potential of explants. Our study shows that not only commercially available charcoal, but also self-produced biochars and their activated variants were capable of inducing changes in growth and proliferation capacity.…”
Section: Discussionmentioning
confidence: 99%